2018
DOI: 10.1515/ncrs-2018-0099
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure ofN-butylpyridinium bis(μ2-dichlorido)-tetrachloridodicopper(II), C18H28N2Cu2Cl6

Abstract: C 9 H14Cl 3 CuN, monoclinic, P21/n (no. 14), a = 9.6625 (6)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The crystal structures are closely related to the existing examples 23,28,33,42 and these data clearly show that the process and approach towards these ILs is highly reproducible, exible, and adaptable. Moreover, like on the previous examples, all structures of the single crystals (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…The crystal structures are closely related to the existing examples 23,28,33,42 and these data clearly show that the process and approach towards these ILs is highly reproducible, exible, and adaptable. Moreover, like on the previous examples, all structures of the single crystals (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…ILPs can be designed to include a number of elements into one compound that can then be used to synthesize nanomaterials. This is particularly interesting when considering the synthesis of compounds with more complex compositions: suitable ILPs can be made to contain all metal ions needed for product formation and thus possibly also provide access to non‐stoichiometric compounds that are not easily accessible otherwise [114,215] . While this concept is just being established, we have recently demonstrated that a wide variety of ILPs with different metal/metal ratios and various metal/metal combinations are accessible [216] .…”
Section: Future Perspectives and Challengesmentioning
confidence: 99%
“…Indeed, we have recently demonstrated that the formation of CuS and CuCo 2 S 4 from ILs produces a surprisingly high electrochemical surface area compared to the same compounds made via other synthetic approaches. [215] This indicates that ILs are not only efficient templates in an interesting temperature range but also that their specific ionic nature may be a tool to engineer surface details that may have an impact on catalytic reactions such as the oxygen (OER) or the hydrogen evolution reaction (HER). Again, the available datasets are far from complete and more work will be needed to (1) understand and (2) control such IL-surface interactions and their role in surface design.…”
Section: Future Perspectives and Challengesmentioning
confidence: 99%
See 2 more Smart Citations